Pengembangan Kontrol Robot Omnidirectional Menggunakan Sensor Gerakan Mpu 6050 Berbasis Internet Of Things (IoT) - Aryo Pratama, Bimo; Deosa Putra Caniago; M. Abrar Masril; Luki Hernando; Muhammad Jufri (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2025)
Robotics is a field that encompasses interdisciplinary sciences, ranging from the mechanics of robot construction, electronics, and control systems to artificial intelligence. Initially, robotics was widespread in industry, often referred to as industrial robots. The Mini Trolley Robot provides a solution to issues related to flexibility in the room. The robot’s operation can be directed using motion sensors. This research aims to develop a controlled exploration system with an IoT-based mobile robot using the MPU6050 motion sensor. This aims to provide a solution to flexibility issues in complex environments without using traditional remote controls. The system uses the ESP32Wroom as the microcontroller, ESP32 Cam for video streaming, a driver module as the driver, DC motors, and a 12V to 5V converter. The ESP32 module allows good connectivity and remote control via a Wi-Fi network. The MPU6050 motion sensor can read tilt angles based on sensor data contained in the MPU6050 module. To access this sensor module, the I2C data line is used. This research employs the waterfall method, which includes stages of determining user requirements, followed by planning, modeling, construction, system delivery to users, and supporting the entire developed software. The motion sensor from the MPU6050 achieves a considerable range from 5 to 15 meters with accurate results, while reaching 19 meters results in a delay of 2 or 3 seconds.